Syzygium jambos Displayed Antibacterial and Antibiotic-Modulating Activities against Resistant Phenotypes - Wamba, Brice E. N. (Evid Based Complement Alternat Med, 2018)
The present study was designed to evaluate the antibacterial activities of methanol extracts of bark and leaves of Syzygium jambos, as well as their synergistic effects with selected antibiotics against drug-resistant Gram-positive and Gram-negative bacteria. The crude extracts were subjected to qualitative phytochemical screening; broth microdilution method was used for antibacterial assays. Phytochemical studies indicate that leaves and bark extracts contained polyphenols, anthraquinones, tannins, and steroids. Extract of the leaves was active against all the 26 strains of Staphylococcus aureus and all the 21 strains of Gram-negative bacteria tested, within the minimum inhibitory concentration (MIC) range of 32–512 μg/mL. The lowest MIC value of 32 μg/mL was obtained with extract of the leaves against Staphylococcus aureus MRSA9 strain. In Gram-negative bacteria, the lowest MIC value of 64 μg/mL was also obtained against Enterobacter aerogenes EA294 and Klebsiella pneumoniae K24 strains. Against S. aureus strains, antibiotic-modulating activity of extracts at MIC/2 towards more than 70% of the tested strains was obtained when leaves and bark extracts were tested in association with chloramphenicol (CHL). This was also the case when leaves extract was combined with CHL, kanamycin (KAN), tetracycline (TET), and erythromycin (ERY) and when bark extract was combined with ciprofloxacin (CIP), TET, and ERY against Gram-negative bacteria. In conclusion, this study demonstrated that Syzygium jambos has antibacterial and antibiotic-modulating activities.